A neo-institutional analysis of the hidden interaction between the Israeli Supreme Court and the Ministry of Finance: the right to healthcare services - Daniel Sperling; Nissim Cohen (BMC, 2018)
Abstract Background Under structural conditions of non-governability, most players in the policy arena in Israel turn to two main channels that have proven effective in promoting the policies they seek: the submission of petitions to the High Court of Justice and making legislative amendments through the Economic Arrangements Law initiated by the Ministry of Finance. Nevertheless, an analysis of the principal trends emerging from the High Court of Justice rulings and legislative amendments through the Economic Arrangements Law indicates that these channels are open to influence, primarily by forces that are essentially neo-liberal. Little is known about the effects of these trends on the right to healthcare services, which in Israel has not been legislated as an independent constitutional law in Basic Laws. Methods We use four major legal cases decided by the Supreme Court of Israel in the past 10 years where the Court reviewed new legislative initiatives proposed by the Economic Arrangements Law in the area of healthcare. We utilize an institutional approach in our analysis. Results A neo-institutional analysis of the legal cases demonstrates that petitions against the Economic Arrangements Law in the area of healthcare services have been denied, even though the Court uses strong rhetoric against that law and the government more generally in addressing issues that concern access to healthcare services and reforms in the healthcare system. This move strengthens the trend toward a neo-liberal public policy and significantly weakens the legal protection of the right to healthcare services. Conclusion In deciding petitions against the Economic Arrangements Law in the area of healthcare, the Supreme Court allows the Ministry of Finance to be a dominant player in the formation of public policy. In doing so, it may be promoting a goal of strengthening its position as a political institution that aspires to increase the public's trust in the judiciary and especially in the Supreme Court itself, in addition to exercising judicial restraint and allowing more leeway to the executive and legislative branches more generally.